Принудительный выкуп земельных участков в публичных интересах как форма прекращения права собственности - Yefremowa, Inna (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an evaluation of the compulsory purchase of the land in the public interest in regards to the article 35 of the Constitution of the Russian Federation. The author present the compulsory purchase in the public interest, including land, as a form of the property right limitation, that should fulfil the selected, established law procedures.
Compulsory purchase of the land in the public interest as a form of the property right limitation
Keywords: compulsory purchase; land property; public interest